2018
DOI: 10.1016/j.ymeth.2018.02.017
|View full text |Cite
|
Sign up to set email alerts
|

The yin and yang of solubilization and stabilization for wild-type and full-length membrane protein

Abstract: Membrane proteins (MP) are stable in their native lipid environment. To enable structural and functional investigations, MP need to be extracted from the membrane. This is a critical step that represents the main obstacle for MP biochemistry and structural biology. General guidelines and rules for membrane protein solubilization remain difficult to establish. This review aims to provide the reader with a comprehensive overview of the general concepts of MP solubilization and stabilization as well as recent adv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 61 publications
0
30
0
Order By: Relevance
“…However, detergent micelles are not ideal membrane protein-supporting platforms. The dynamic equilibrium between detergent monomers and micelles, and differences in physicochemical properties between detergent micelles and biomembranes (e.g., curvature, lateral pressure profile, thickness) are some of the causes of the decrease in membrane-protein stability in detergents [2][3][4][5] . In addition, the structure and function of membrane proteins can be affected when the proteins are in detergent micelles [6][7][8][9][10][11] , which is leading to the increased use of biomembrane-based platforms.…”
mentioning
confidence: 99%
“…However, detergent micelles are not ideal membrane protein-supporting platforms. The dynamic equilibrium between detergent monomers and micelles, and differences in physicochemical properties between detergent micelles and biomembranes (e.g., curvature, lateral pressure profile, thickness) are some of the causes of the decrease in membrane-protein stability in detergents [2][3][4][5] . In addition, the structure and function of membrane proteins can be affected when the proteins are in detergent micelles [6][7][8][9][10][11] , which is leading to the increased use of biomembrane-based platforms.…”
mentioning
confidence: 99%
“…The evaluation of purified protein quality is crucial in any protein production process and should be accurately performed to avoid irreproducible and misleading observations in the subsequent studies (Raynal et al 2014). After production, MP need to be efficiently solubilized (recently reviewed by Hardy et al 2018 andPopot 2018) and purified (Pandey et al 2016), from which their quality in terms of purity, homogeneity, activity, and structural conformity should be assessed (Oliveira and Domingues 2018;Raynal et al 2014). In this review, generic guidelines and host characteristics aiming an accurate choice of the host expression system that better suits particular needs will be initially overviewed in this review, and then we discuss important advances reported at the level of the upstream stage of recombinant MP production processes using E. coli, P. pastoris, and mammalian cell lines, representative of major expression systems used for protein expression.…”
Section: Recombinant Membrane Protein Biosynthesismentioning
confidence: 99%
“…Therefore, there is high priority in understanding MPs because of their importance to improve therapeutics for many medical conditions. Yet, progress in the MP field has been slow in comparison to that of other biomolecules because of difficulties in overexpression, membrane extraction, and purification, which frequently vary even for proteins within the same family (Seddon et al, 2004;Hardy et al, 2018). Maintaining an environment conducive to MP function and stability for evaluation in vitro is still a major challenge.…”
Section: Introductionmentioning
confidence: 99%
“…In most cases, studies of purified MPs include expression through recombinant methods followed by extraction from membranes using detergents to produce the proteins solubilized in detergent micelles (Figure 1; Seddon et al, 2004;Hardy et al, 2018;Stroud et al, 2018). Once solubilized, purification can proceed using methodologies typically employed to purify soluble proteins, but in the continuous presence of detergent to keep the MP in a soluble state.…”
Section: Introductionmentioning
confidence: 99%